Clinical, socio-demographic profile and outcome of neurocysticercosis in children: a hospital based study - Saurabh, Kumar; Ranjan, Shilpi; Verma, Neelam (International Journal of Research in Medical Sciences, 2017)
Background: Neurocysticercosis (NCC) is perhaps the most common parasitic infection of human nervous system. The objective of this study was to study the spectrum of clinical, socio-demographic profile and treatment outcome of 60 paediatric neurocysticercosis cases over a mean duration of two years from September 2006-August 2008. Methods: Diagnosis was made mainly on the basis of clinical features, ring enhancing lesions on Computed Tomography scan of brain and exclusion of other causes. Patients were treated with Albendazole for 28 days, Prednisolone and anticonvulsant. Results: 10-14 years was the most affected age group with no sex predilection. Seizure was the most common initial presentation (86.66%) followed by headache and vomiting. Generalized tonic clonic seizure was the most common type of seizure. Four patients returned with relapse. Conclusions: Neurocysticercosis is a disease of lower socioeconomic group with poor sanitation and poor hand hygiene. Generalized tonic clonic seizure is the main presentation. Anticysticercal therapy has a good outcome.